2016
DOI: 10.3390/ijms17050677
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Pathway: A Potential Target for the Treatment of Depression

Abstract: During the past decade, accumulating evidence from both clinical and experimental studies has indicated that erythropoietin may have antidepressant effects. In addition to the kidney and liver, many organs have been identified as secretory tissues for erythropoietin, including the brain. Its receptor is expressed in cerebral and spinal cord neurons, the hypothalamus, hippocampus, neocortex, dorsal root ganglia, nerve axons, and Schwann cells. These findings may highlight new functions for erythropoietin, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 208 publications
(203 reference statements)
2
37
0
1
Order By: Relevance
“…These effects appear in a relatively short period. Some articles have reported that the effects appear 3 or 4 days after EPO administration in experiments with animals or humans . In our case, we concluded that the activities of daily living had improved immediately due to the antidepressant effects of EPO, and earlier than the improvement in anemia.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…These effects appear in a relatively short period. Some articles have reported that the effects appear 3 or 4 days after EPO administration in experiments with animals or humans . In our case, we concluded that the activities of daily living had improved immediately due to the antidepressant effects of EPO, and earlier than the improvement in anemia.…”
supporting
confidence: 48%
“…As it promotes hematopoiesis, it is clinically used for renal anemia. In recent years, EPO receptors have been detected in the central nervous system; EPO activate multiple downstream signaling pathways and this activation may develop antidepressant effects . These effects appear in a relatively short period.…”
mentioning
confidence: 99%
“…DMOG also prevented microglial and glial activation (Iba-1 and GFAP immunolabeling). Although we have not evaluated it, other researchers have shown that HIF-1a and its targets (e.g., erythropoietin) can exert antiapoptotic and anti-inflammatory effects through ERK-1/2 signaling and activation of PKB pathway (55)(56)(57)(58). Further studies are needed to clarify the molecular mechanisms underlying the neuroprotective effect of DMOG.…”
Section: Discussionmentioning
confidence: 93%
“…EPO can phosphorylate Akt at serine 473 to activate Akt (37, 64, 87, 88). EPO signaling through Akt activation has been shown to protect against hypoxia-reoxygenation stress (79) and EPO may control intracellular calcium levels to preserve mitochondrial function (31, 67, 8991).…”
Section: Trpv1 and Erythropoietinmentioning
confidence: 99%